Interaction Between National and International Regulations on Human Economic Rights - Baesu, Valeriu (Acta Universitatis Danubius. Juridica, 2022)
Human economic rights can be considered as fundamental rights that characterize the well-being of the person, the state of attachment of the individual characterized by a full economic satisfaction that allows him to assert himself both as a separate subject and as a collective member of a community organized by people, whereas fundamental human rights as subjective rights of citizens, essential for their life, freedom and dignity, indispensable for the free development of the human personality.